Medialny warsztat nauczyciela muzyki = The music teacher`s media tools and skills - Kataryńczuk-Mania, Lidia (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents the possibilities of using the didactic potential of information technologies by the teacher in music classes. It shows the importance of using a computer in the process of education. Computer suitability for teaching increases together with growing technical capacities to register textual, graphic, and sound information; store information; copy and present it; as well as facilitate communication between information users in local and global networks. The authors of the article present also information and media competences of the teacher, as well as selected music software.
Keywords: kompetencje nauczyciela; muzyczne media; oprogramowanie komputerowe do tworzenia audycji muzycznych; teacher`s competences; music media; computer software for creating